INTEGRATING ISLAMIC MARKETING AND GREEN MARKETING THROUGH MAQASHID SHARIAH: A CONCEPTUAL FRAMEWORK FOR SUSTAINABLE VALUE CREATION - Kumara Adji Kusuma; Aidah Safira Maharani; Rara Novalia; Mochamad Rizal Yulianto; Herlinda Maya Kumala Sari (Antis Publisher, 2026)
Objective: The growing urgency of environmental sustainability has challenged conventional marketing paradigms, including green marketing, which is often criticized for its instrumental and profit-driven orientation. Simultaneously, Islamic marketing offers a value-based framework grounded in ethical and spiritual principles but remains underexplored in addressing ecological concerns. This study aims to develop an integrative conceptual framework that bridges Islamic marketing and green marketing through the lens of maqashid shariah. Method: Using a structured literature review and critical synthesis approach, this study identifies a theoretical gap between sustainability-driven marketing and faith-based ethical systems. Results: The findings reveal that while green marketing emphasizes environmental responsibility, it lacks a transcendent moral foundation. Conversely, Islamic marketing provides a holistic ethical system but has not been fully operationalized in environmental contexts. Novelty: This study proposes a maqashid shariah-based framework that integrates ecological sustainability into Islamic marketing by aligning environmental protection with the preservation of life (nafs), lineage (nasl), and wealth (mal). The framework introduces the concept of Islamic Green Marketing (IGM) as a value-driven and sustainability-oriented paradigm. The study contributes to the literature by offering a novel theoretical integration and provides managerial implications for halal industries and Islamic social finance institutions in advancing sustainable practices.